Social Media for Learning in Higher Education 2015 Conference Proceedings 2016
DOI: 10.7190/socmedhe/2015/8
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking for Learning in Higher Education: Capitalising on Social Capital

Abstract: This study explores the evolution of student-led social networking groups initiated and sustained by a cohort of undergraduate students over a 3-year time frame. The study contributes to this growing area of research by exploring the impact of peer-led, peer-supported informal learning through social media networks. Social capital is a useful lens through which to understand the findings, and particularly in interpreting descriptions of the evolution of the group over time. The findings suggest that students b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Under this circumstance, the escalating prevalence of social media addiction among the younger generations in China, characterized by a gradual erosion of love relationship closeness, harmony, and satisfaction, constitutes a complex and exigent problem that demands rigorous investigation. The dualistic nature of social mediasimultaneously a tool for connection and a catalyst for disconnection-makes it a perplexing issue requiring nuanced understanding (Weinstein & Siste, 2022;Hartley & Kassam, 2016). It is this very contradiction that may foster a deterioration in the quality of life and undermine the happiness and satisfaction derived from relationships (Aboujaoude et al, 2022;Nehring & Kerrigan, 2019).…”
Section: Research Background and Problem Statementmentioning
confidence: 99%
“…Under this circumstance, the escalating prevalence of social media addiction among the younger generations in China, characterized by a gradual erosion of love relationship closeness, harmony, and satisfaction, constitutes a complex and exigent problem that demands rigorous investigation. The dualistic nature of social mediasimultaneously a tool for connection and a catalyst for disconnection-makes it a perplexing issue requiring nuanced understanding (Weinstein & Siste, 2022;Hartley & Kassam, 2016). It is this very contradiction that may foster a deterioration in the quality of life and undermine the happiness and satisfaction derived from relationships (Aboujaoude et al, 2022;Nehring & Kerrigan, 2019).…”
Section: Research Background and Problem Statementmentioning
confidence: 99%
“…For example, studies have demonstrated the benefits of harnessing technology to enhance mentorship programs that increase social capital of disadvantaged populations. [8][9][10][11] This approach already is in progress, bolstered by advances made in digital communications during the coronavirus disease 2019 pandemic. 12 Student-led networking groups that connect remotely have been shown to build social capital bonds and bridges that facilitate collaborative learning, relationship building, and information sharing.…”
Section: Acquiring Social Capital As a Uim Studentmentioning
confidence: 99%
“…12 Student-led networking groups that connect remotely have been shown to build social capital bonds and bridges that facilitate collaborative learning, relationship building, and information sharing. [8][9][10][11] There are existing online UIM student networks that individual dermatologists, institutions, and national organizations can partner with to facilitate the construction of bridges between these UIM student groups and dermatologists who can provide accurate, high-yield information and professional networking; however, one limitation of this suggestion is the disparate access to technology in the UIM community.…”
Section: Acquiring Social Capital As a Uim Studentmentioning
confidence: 99%